Effects of Evapotranspiration on Mitigation of Urban Temperature by Vegetation and Urban Agriculture - Guo-yu QIU; Hong-yong LI; Qing-tao ZHANG; Wan CHEN; Xiao-jian LIANG; Xiang-ze LI (Journal of Integrative Agriculture, 2013)
The temperature difference between an urban space and surrounding non-urban space is called the urban heat island effect (UHI). Global terrestrial evapotranspiration (ET) can consume 1.4803×1023 joules (J) of energy annually, which is about 21.74% of the total available solar energy at the top of atmosphere, whereas annual human energy use is 4.935×1020 J, about 0.33% of annual ET energy consumption. Vegetation ET has great potential to reduce urban and global temperatures. Our literature review suggests that vegetation and urban agricultural ET can reduce urban temperatures by 0.5 to 4.0°C. Green roofs (including urban agriculture) and water bodies have also been shown to be effective ways of reducing urban temperatures. The cooling effects on the ambient temperature and the roof surface temperature can be 0.24-4.0°C and 0.8-60.0°C, respectively. The temperature of a water body (including urban aquaculture) can be lower than the temperature of the surrounding built environment by between 2 and 6°C, and a water body with a 16 m2 surface area can cool up to 2 826 m3 of nearby space by 1°C. Based on these findings, it can be concluded that the increase of evapotranspiration in cities, derived from vegetation, urban agriculture, and water body, can effectively mitigate the effect of urban heat islands.